Soialogical Explanation Of Cultural Capital On Social Adjustment (Example: Residents Of Residential Complexes In Isfahan) - Mohammad Reza Nezarati zadeh; Reza Esmaeili; Asghar Mohammadi (جغرافیا و آمایش شهری منطقه‌ای, 2020)
Changing the spatial land use structure of cities has aggravated social issues such as reducing social adjustment among residents of urban residential complexes. Therefore, in the present study, the relationship between Social Capital with social adjustment among residents of residential complexes in Isfahan in 2019 The study was conducted with a combination of sociological and psychological theories. Individuals and households living in residential complexes in Isfahan, which is about 1155,800 people and 385 residents, were selected as a sample according to the Cochran's formula. Factor analysis, path analysis and structural equation model analysis as well as ANOVA test using SPSS and AMOS software were used for data analysis. According to the research results, there is an inverse and significant relationship between cultural capital and social adjustment of residents. There is a significant difference between education and social adjustment. The lowest level of social adjustment is in postgraduate and higher and the highest level of social adjustment is in cycle and middle school. The findings also showed that there is no significant difference between the length of residence and employment status with social adjustment